5‑Formylcytosine Yields DNA–Protein Cross-Links in Nucleosome Core Particles - Li, Fengchao; Zhang, Yingqian; Bai, Jing; Greenberg, Marc M; Xi, Zhen; Zhou, Chuanzheng (Journal of the American Chemical Society, 2017)
In situ generation of 5-formylcytosine (5fC) in nucleosome core particles (NCPs) reveals that 5fC leads to essential DNA–protein cross-links (DPCs). Mechanistic studies using chemical models and mutated histones demonstrate that DPCs form reversibly between the formyl function of 5fC and primary amines on histones. These results suggest that DPC formation from 5fC in chromatin occurs in addition to its role in DNA demethylation.